2020
DOI: 10.3390/cancers12102727
|View full text |Cite
|
Sign up to set email alerts
|

Promising Applications of Tumor Spheroids and Organoids for Personalized Medicine

Abstract: One of the promising directions in personalized medicine is the use of three-dimensional (3D) tumor models such as spheroids and organoids. Spheroids and organoids are three-dimensional cultures of tumor cells that can be obtained from patient tissue and, using high-throughput personalized medicine methods, provide a suitable therapy for that patient. These 3D models can be obtained from most types of tumors, which provides opportunities for the creation of biobanks with appropriate patient materials that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 143 publications
(190 reference statements)
1
77
0
Order By: Relevance
“…[35,37] The epithelialmesenchymal interactions have been shown to guarantee the stability of the 3D culture at long-term (at least 1 year) [35] mostly due to in vitro expansion of immature progenitor populations, replenishing dying cells; this type of interaction is one of the characteristics presented by organoids, while not all spheroids are viable for longer periods in culture for not necessarily presenting regular morphology and also due to spheroid transferring, what can cause disaggregation. [38,39] of cells to self-organize spontaneously, deposit extracellular matrix and form specific microenvironments. [26,[40][41][42] In oncology research, several trials have shown that while monolayer tumors were sensitive to the action of several chemotherapeutic agents, the same cells, when grown as spheroids, were resistant to them.…”
Section: Particularities Of the Most Common 3d Cultures: Spheroids And Organoidsmentioning
confidence: 99%
“…[35,37] The epithelialmesenchymal interactions have been shown to guarantee the stability of the 3D culture at long-term (at least 1 year) [35] mostly due to in vitro expansion of immature progenitor populations, replenishing dying cells; this type of interaction is one of the characteristics presented by organoids, while not all spheroids are viable for longer periods in culture for not necessarily presenting regular morphology and also due to spheroid transferring, what can cause disaggregation. [38,39] of cells to self-organize spontaneously, deposit extracellular matrix and form specific microenvironments. [26,[40][41][42] In oncology research, several trials have shown that while monolayer tumors were sensitive to the action of several chemotherapeutic agents, the same cells, when grown as spheroids, were resistant to them.…”
Section: Particularities Of the Most Common 3d Cultures: Spheroids And Organoidsmentioning
confidence: 99%
“…Each model (spheroids vs. organoids) has its own advantages and disadvantages as reviewed by Gilazieva et al [ 64 ]. For example, spheroid models are thought to be enriched for a cell population with a CSC phenotype; however, these models may not fully recapitulate the tumor architecture [ 64 ]. On the other hand, organoid models are more architecturally and functionally similar to their parental tumors and can be maintained in culture long term through passaging [ 64 ].…”
Section: Emergence Of 3d Cell Culture Models For Drug-testing In Omentioning
confidence: 99%
“…For example, spheroid models are thought to be enriched for a cell population with a CSC phenotype; however, these models may not fully recapitulate the tumor architecture [ 64 ]. On the other hand, organoid models are more architecturally and functionally similar to their parental tumors and can be maintained in culture long term through passaging [ 64 ]. For use in drug testing assays, particular consideration should be given to the limitations associated with each model.…”
Section: Emergence Of 3d Cell Culture Models For Drug-testing In Omentioning
confidence: 99%
See 1 more Smart Citation
“…Applications of spheroids from different cellular sources have been reviewed extensively elsewhere and hence we mainly focus on tumor-derived organoids. However, we include recent literature on tumor-derived spheroids in respective sections [ 10 , 11 , 12 ]. Finally, we conclude with merits and challenges of organoid technology in cancer biology.…”
Section: Introductionmentioning
confidence: 99%